Localised dystopia in Croatian and Serbian cinema - Gilić, Nikica (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Genre production is often easily localised in various cultures, but localisations of science fiction seem particularly interesting, due to the technological sources of the genre imagery and typical narrative structures. Localisation to a less technologically-oriented society, such as post-yugoslav Croatia and Serbia, are a very good example, since in such films as The Show Must Go On (by Nevio Marasović) and Technotise – Edit & I (by Aleksa Gajić and Nebojša Andrić) allegorical science fiction deals directly with local problems and narrations, such as Croatia’s obsession with modernisation and Western-European identity (in Marasović’s film) and Serbia’s traumatic relation with Slobodan Milošević’s regime and national pride (in Gajić’s and Andrić’s animated feature film). The experimental concept of Unknown Energies, Unidentified Feelings (by Dalibor Barić and Tomislav Babić) provides another model of dealing with genre structures in a local context, since it directly develops the early-1970s model of connecting experimental cinema with the technological obsessions of the era (important for entire Yugoslavia through the GEFF festival) into a contemporary experimental animated dystopia.